A rare pathology: Levoatriocardinal vein - Öykü Tosun; Murat Saygı; Taner Kasar; Pelin Ayyıldız; Aysel Türkvatan; Yakup Ergül; Ender Ödemiş; Alper Güzeltaş (KARE Publishing, 2016)
Objective: Levoatriocardinal vein (LACV) is a rare cardiac pathology that represents a connection between the pulmonary venous and cardinal systems. The aim of the present study was to discuss morphological and clinical characteristics, as well as diagnostic methods, of experience with LACV. Methods: Records of 11 patients (4 male, 7 female; mean age 79+-1.83 days; range 1-390 days) diagnosed with LACV between 2010 and 2014 were retrospectively reviewed. Presence of LACV was confirmed with echocardiography. The primary obstructive lesion associated with cardiac defects and the integrity of the interatrial septum was identified in each patient with left-sided obstruction. Results: Mean weight was 4.4+-0.4 kg (range: 2-8). Age at presentation was under 1 year in 82% of patients. Nine patients had left-sided obstruction, and 2 had normal intracardiac anatomy and pulmonary venous return. In patients with left-sided obstruction, LACV was initially demonstrated with echocardiographic evaluation, performed in apical 4-chamber, high parasternal, and subcostal views. Atrial septum was restrictive or intact in patients with left-sided obstructions. LACV originated directly from the left atrium in all patients. Conclusion: Levoatriocardinal vein is an extremely rare cardiac pathology, presenting almost exclusively in patients with left-sided obstructive lesions. In patients with left-sided obstructions, LACV must be kept in mind. It may also present in patients with normal intracardiac anatomy and pulmonary venous return.